Collaborative language learning and teaching - Nunan, David (Cambridge [England] Cambridge University Press, 1992)
Collaborative Language Learning and Teaching is written for teachers, teacher educators and researchers who are interested in experimenting with alternative ways of organising teaching and learning, and who wish to create an environment in which teachers, learners and researchers can work together and learn from one another. This wide-ranging collection of papers focuses on issues such as: The central characteristics of a collaborative approach to classroom research - Appropriate theoretical models of language and learning for informing collaborative research Appropriate research methods, tools and techniques for collaborative investigations - Classroom tasks and patterns of organisation which facilitate cooperative learning - Organisational patterns which underlie successful collaborative teaching. The classroom-oriented studies on which the collection is based provide models for readers who wish to experiment with these ideas in their own context.
Experiential language learning : second language learning as cooperative learner education / Viljo Kohonen -- Literacy skills or literate skills? : considerations for ESL/EFL learners / Shirley Brice Heath -- Collaboration : constructing shared understandings in a second language classroom / Donald Freeman -- Context and cooperation in academic tasks / Bernard Mohan and Sondra Marshall Smith -- Collaborative writing as a literacy event : implications for ESL instruction / Denise E. Murray -- Collaborative language teaching : a co-investigation / Nora B. Shannon and Bonnie Meath-Lang -- Team teaching : a case study from Japan / Peter Sturman -- Some reflections on collaborative language teaching / Kathleen M. Bailey, Ted Dale and Benjamin Squire -- The power of observation : "Make a wish, make a dream, imagine all the possibilities!" / Jerry G. Gebhard and Akiko Ueda-Montonaga -- A teacher research group in action / Sandra R. Schecter and Rafael Ramirez -- Putting a process syllabus into practice / Roger Budd and Tony Wright -- Toward a collaborative approach to curriculum development : a case study / David Nunan.
Keywords: Language and languages -- Study and teaching; Group work in education